The antidiabetic activity of curry leaves “Murraya koenigii” on the glucose levels, kidneys, and islets of langerhans of rats with streptozotocin induced diabetes - Al-Ani, Imad Matloub Dally; Santosa, Rahajoe Imam; Yankuzo, Muhammad H.; Saxena, Anil Kumar; Alazzawi, Khalid S. (Universitas Indonesia, 2017)
Background: The aims of this study were to explore the antihyperglycemic effect of curry leaves, Murraya koenigii “MK” aqueous extract, and to examine its possible protective effects on the islets of Langerhans and kidneys of streptozotocin (STZ) diabetic rats. Methods: Thirty healthy adult male Sprague Dawley rats were randomized into five groups (n=6); normal control, normal treated with “MK” control, diabetic control (non-treated with “MK”), diabetic treated with 200 mg/kg MK aqueous leaf extract and diabetic treated with 400 mg/kg MK aqueous leaf extract. Blood glucose levels and body weight were monitored gravimetrically. The animals were sacrificed on the 30th day; the kidney and pancreatic tissues were processed for histological studies. Results: The diabetic group showed considerable loss of body weight and increase in blood glucose levels and degeneration of the glomeruli and renal convoluted tubules and atrophied islets with disintegration of β-cells. Treatment of diabetic rats with MK extract showed significant (p < 0.001) improvement in blood glucose levels and body weight gain. The MK extract also caused an improvement in tissue injury induced by STZ injection in the kidney and islets of Langerhans. Conclusions: These findings highlighted the beneficial effects of MK aqueous extract against cellular oxidative damage in STZ-induced diabetic rats.